Armed Conflict-induced Displacement and Human Trafficking in the Sahel: Organised crime, vulnerabilities, and the accountability of non-state armed groups - Ogunniyi, Daniel (Anti-Trafficking Review, 2024)
Although organised criminal networks and non-state armed groups (NSAGs) have historically exploited conflict situations to commit various crimes, the extent of human trafficking by these entities in the Sahel has barely been interrogated in academic literature. In principle, while states have an obligation to criminalise trafficking in persons, problems arise where the state has lost parts of its territory to NSAGs or is facing ongoing conflicts with such groups. Boko Haram, for instance, controlled a large swath of territory in Northeast Nigeria from 2009 to 2015, with evidence of human trafficking. Therefore, this paper examines two specific aspects of human trafficking in the Sahel conflicts: trafficking by organised criminals and trafficking by NSAGs, especially terrorist organisations. It argues that while domestic laws may be useful in combating trafficking linked to organised criminal networks, the traditional state-centric approach to human rights protection makes human trafficking governance more complicated where NSAGs are involved, especially where they exercise territorial control. The paper unpacks these complexities and highlights the deficits in existing international law treaties. It argues that customary international law could provide a solution to the anti-trafficking governance challenge in the Sahel and makes a case for the adoption of an anti-trafficking Deed of Commitment within the Geneva Call mechanism.